CORPORATE GOVERNANCE DAN INTERDEPENDENSI ANTARA LEVERAGE, PROFITABILITAS SERTA KEBIJAKAN DIVIDEN DALAM MENCAPAI NILAI PERUSAHAAN - Muhamad Umar Mai (Jurnal Keuangan dan Perbankan, 2015)
This research aimed to find out and to analyze the role of corporate governance mechanism in utilizing theinterdependence among funding decisions, financial performance, and dividend policy in an attempt to increasethe value of the company. The study was conducted at the manufacturing companies listed in Indonesia StockExchange, with the observation in the period of 2000-2012. A pooled data with a total of 290 companies wereanalyzed using path analysis. This study proved that the escalation in the value of the company was mainlyinfluenced by the companys ability to increase the profitability and dividend payments. Institutional ownershipand board size as a proxy of corporate governance mechanism played a crucial part to encourage companiesto enhance its return on equity, while the independent board persuaded the companies to amplify itsdividend payments. The Board size showed a strong role in inspiring companies to improve its profitability,and it had a positive effect on firm value.